2010
DOI: 10.1002/pc.20963
|View full text |Cite
|
Sign up to set email alerts
|

Load bearing properties of three‐component polymer composites

Abstract: Metal or solid polymer anchors are used as the load transfer components for foam and foam composites when they are used as the structural elements in design. The traditional method of fixation of these components is by fastening and adhesion. In this study, anchors were created in the form of inserts and were imbedded in the sandwich composite during the foaming process, resulting in the manufacture of three‐component composite. Flexure tests were conducted to study the effect of different geometries (rectangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Sandwich composites with tapered inserts showed better load bearing properties compared to rectangular and cylindrical inserts of the same length. The results showed the reduced sandwich stiffness is a function of crack length Ahmed et al (2010). When leaf inserts were introduced, better adhesion properties were found when compared with other insert geometries Ahmed et al (2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sandwich composites with tapered inserts showed better load bearing properties compared to rectangular and cylindrical inserts of the same length. The results showed the reduced sandwich stiffness is a function of crack length Ahmed et al (2010). When leaf inserts were introduced, better adhesion properties were found when compared with other insert geometries Ahmed et al (2011).…”
Section: Introductionmentioning
confidence: 96%
“…The results showed that specific strength of 3D woven composite inserts is higher than that of aluminum inserts, beyond significant weight saving of material. Ahmed et al (2010) and Ahmed et al (2011) analyzed the adhesion properties of sandwich composites having aluminum inserts with different geometries (rectangular, cylindrical and tapered) under flexural loading. It was reported that the failure stress and adhesion properties were dependent on the embedded insert length and geometry.…”
Section: Introductionmentioning
confidence: 99%